Determination of the geometric parameters of the defects based on the tomographically obtained data and their influence on the fatigue behavior of the S960 with laser cladded protective layers (Fracture and Structural Integrity, 2024)
This article deals with identifying defects of layered high strength steel materials with the help of tomography measurement. Test samples were made of S960 High Strength Steel to which layers of either aluminium bronze, hardchrome, cobalt alloy or stainless steel were applied by a laser cladding technology. The experimental campaign included a study of morphometric parameters of internal defects in and near the bi-material interface region using X-ray micro-tomography and their potential influence on the fatigue behavior during a three-point bending test.
Keywords: S960; Tomography; laser cladded; Aluminum bronze; Cobalt alloy; stainless steel